Analysis of the Strategy for Developing Outpatient Services at the Locus Medical Hub Clinic Using SWOT Analysis - Achmad Subahtiyar; Pipit Festi Wiliyanarti; Mundakir; Agus Chairul Anab (Universitas Muhammadiyah Surabaya, 2026)
Increasingly fierce competition in the healthcare sector requires clinics to continuously improve the quality of their services and organizational competitiveness. Outpatient services are one of the primary services that play a crucial role in enhancing patient satisfaction, the number of visits, and the clinic’s operational sustainability. Therefore, an appropriate development strategy is needed based on an analysis of the organization’s internal and external conditions. This study analyzes the development strategy for outpatient services at Locus Medical Hub Clinic using SWOT analysis and formulates an appropriate development strategy. This research employs a qualitative approach with a case study design. The research informants consist of management, doctors, nurses, administrative staff, and outpatient patients selected using purposive sampling, totaling 30 respondents. Data collection was conducted through in-depth interviews, observation, documentation, and Focus Group Discussions (FGDs). Data analysis was performed using the Internal Factor Analysis Summary (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, and SWOT Matrix. The analysis results show an IFAS score of 3.04 and an EFAS score of 3.15. The clinic’s key strengths include competent healthcare staff, fast and friendly service, a digital registration system, and a strategic location. Key opportunities stem from the growing demand for healthcare services, advancements in healthcare technology, and opportunities for collaboration with various parties. The SWOT analysis results place Locus Medical Hub Clinic in Quadrant I, indicating a strong organizational condition with high development potential. The recommended strategy is an aggressive strategy (SO) that leverages internal strengths to capitalize on external opportunities. This strategy includes the development of technology-based flagship services, improving service quality, optimizing digital systems, enhancing human resource competencies, and expanding strategic partnerships to improve the quality of outpatient care and the competitiveness of Locus Medical Hub Clinic.